A review of the status and distribution of the Bornean Bristlehead - Christopher C Witt; Frederick H Sheldon (Indonesian Ornithologists’ Union, 1994)
We compiled all documented records of Bornean Bristlehead Pityriasis gymnocephata to determine what is known about the life-history and distribution of this enigmatic species. Pityriasis is a relict cracticid, related to the Australian magpies and butcherbirds. It is a highly social species and widespread throughout Borneo in forests below 1000m elevation, but rarely encountered.